1950
DOI: 10.1080/00049535008256031
|View full text |Cite
|
Sign up to set email alerts
|

Studies of experimentally induced disturbance

Abstract: The following three studies report some factors involved in and methods of measuring experimentally induced disturbance. The first concerns a relatively simple variable operating at the time disturbance is created ; the second deals with the effect of a 'therapy' applied after the creation of a more complex kind of disturbance ; the third examines methods of measurement, since the first two studies raised doubts about the best means of representing degree of disturbance in quantitative terms. I. Adaptive and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1955
1955
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Most studies of behavioral control have allowed the subject to modify (or at least to believe that he could modify) the objective nature of the threatening event. For example, subjects have been allowed (a) to prevent entirely or at least avoid some instances of a noxious stimulus, say, by having punishment contingent upon the performance of some task (e.g., Averill & Rosenn, 1972;Bowers, 1968;Glass & Singer, 1972;Houston, 1972); (b) to interpose rest periods or take time out from a series of noxious stimuli (Hokanson, DeGood, Forrest, & Brittain, 1971); (c) to terminate prematurely (escape) a noxious stimulus (Bandler, Madaras, & Bern, 1968;Champion, 1950;Elliot, 1969;Geer, Davison, & Gatchel, 1970;Geer & Maisel, 1972); or (d) to limit the intensity of a noxious stimulus (as when subjects select the level of shock they will tolerate in an experiment-cf. previous discussion).…”
Section: Stimulus Modificationmentioning
confidence: 99%
“…Most studies of behavioral control have allowed the subject to modify (or at least to believe that he could modify) the objective nature of the threatening event. For example, subjects have been allowed (a) to prevent entirely or at least avoid some instances of a noxious stimulus, say, by having punishment contingent upon the performance of some task (e.g., Averill & Rosenn, 1972;Bowers, 1968;Glass & Singer, 1972;Houston, 1972); (b) to interpose rest periods or take time out from a series of noxious stimuli (Hokanson, DeGood, Forrest, & Brittain, 1971); (c) to terminate prematurely (escape) a noxious stimulus (Bandler, Madaras, & Bern, 1968;Champion, 1950;Elliot, 1969;Geer, Davison, & Gatchel, 1970;Geer & Maisel, 1972); or (d) to limit the intensity of a noxious stimulus (as when subjects select the level of shock they will tolerate in an experiment-cf. previous discussion).…”
Section: Stimulus Modificationmentioning
confidence: 99%
“…Increase in speed measured by WA-B does not show significant correlations with increase in conductance. The work of Freeman & Pathman (1942) and Champion (1950) would lead us to expect that an increase in motor movement would result in a dissipation of autonomic disturbance. In the case of G.S.R.…”
Section: Inertmentioning
confidence: 99%
“…A number of studies (Champion, 1950;Corah & Boffa, 1970;Bowers, 1968;Houston, 19721 Szpiler & Epstein, 1976) have found that subjects reported less stress when they believed they had behavioral control in a situation (i.e., they could terminate or avoid the electrical shock). A number of researchers have found that control reduces arousal as the subject anticipates receiving shock (Geer et al, 1970;Szpiler & Epstein, 1976).…”
Section: Nature and Theory Of Uncontrollabilitymentioning
confidence: 99%